1996
DOI: 10.1126/science.273.5278.1109
|View full text |Cite
|
Sign up to set email alerts
|

Role of Postreplicative DNA Mismatch Repair in the Cytotoxic Action of Thioguanine

Abstract: It is proposed here that the delayed cytotoxicity of thioguanine involves the postreplicative DNA mismatch repair system. After incorporation into DNA, the thioguanine is chemically methylated by S-adenosylmethionine to form S6-methylthioguanine. During DNA replication, the S6-methylthioguanine directs incorporation of either thymine or cytosine into the growing DNA strand, and the resultant S6-methylthioguanine-thymine pairs are recognized by the postreplicative mismatch repair system. Azathioprine, an immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
281
2
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(296 citation statements)
references
References 20 publications
10
281
2
3
Order By: Relevance
“…6A,B). Our findings are further supported by recent evidence showing that treatment of cells with 6-thioguanine, which is believed to exert its cytotoxicity via a mechanism analogous to MNNG (Swann et al 1996), also results in the accumulation of MMR-dependent single-strand DNA breaks (Yan et al 2003).…”
Section: Discussionsupporting
confidence: 77%
“…6A,B). Our findings are further supported by recent evidence showing that treatment of cells with 6-thioguanine, which is believed to exert its cytotoxicity via a mechanism analogous to MNNG (Swann et al 1996), also results in the accumulation of MMR-dependent single-strand DNA breaks (Yan et al 2003).…”
Section: Discussionsupporting
confidence: 77%
“…The ®ndings that increased level of Pol b in CHO cells produced hypersensitivity to 6-TG and increased incorporation of 6-TG into DNA as compared to its isogenic control cell line strongly suggest that the overproduced enzyme in the 2008/C13*5.25 cells may play a role in the hypersensitivity phenotype toward 6-TG. Extensive work have demonstrated the role of postreplicative mismatch repair in the toxicity of this agent (Swann et al, 1996), but it is unlikely that this process explains the data observed here since the speci®c cell lines used in this study are not defective in mismatch repair.…”
Section: Discussioncontrasting
confidence: 43%
“…O 6 -alkylguanine adducts are induced by a variety of SN1-alkylating agents, including several drugs used for cancer chemotherapy (34). Another drug used in chemotherapy, 6-thioguanine, also produces G adducts that signal apoptosis via MMR (9,35). Consequently, many tumors deficient in MMR become resistant to these drugs, presumably because they no longer signal apoptosis following therapy-induced DNA damage.…”
Section: Resultsmentioning
confidence: 99%